2011
DOI: 10.1242/dev.051912
|View full text |Cite
|
Sign up to set email alerts
|

F3/contactin and TAG1 play antagonistic roles in the regulation of sonic hedgehog-induced cerebellar granule neuron progenitor proliferation

Abstract: SUMMARYModulation of the sonic hedgehog (SHH) pathway is a crucial factor in cerebellar morphogenesis. Stimulation of granule neuron progenitor (GNP) proliferation is a central function of SHH signalling, but how this is controlled locally is not understood. We show that two sequentially expressed members of the contactin (CNTN) family of adhesion molecules, TAG1 and F3, act antagonistically to control SHH-induced proliferation: F3 suppresses SHH-induced GNP proliferation and induces differentiation, whereas T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 62 publications
(105 reference statements)
1
58
0
Order By: Relevance
“…4). Likewise, in contrast to its role in the cortical ventricular zone (Bizzoca et al, 2012), the lamina-specific expression of F3/contactin in the EGL suppresses Shh-dependent proliferation and is antagonised by its binding partner Tag1 (Xenaki et al, 2011), the deletion of which leads to ectopic subpial granule cell clusters in adult mice. Correspondingly, premature misexpression of F3/contactin attenuates granule cell progenitor proliferation (Bizzoca et al, 2003).…”
Section: Balancing Proliferation and Differentiation In The Externalmentioning
confidence: 99%
“…4). Likewise, in contrast to its role in the cortical ventricular zone (Bizzoca et al, 2012), the lamina-specific expression of F3/contactin in the EGL suppresses Shh-dependent proliferation and is antagonised by its binding partner Tag1 (Xenaki et al, 2011), the deletion of which leads to ectopic subpial granule cell clusters in adult mice. Correspondingly, premature misexpression of F3/contactin attenuates granule cell progenitor proliferation (Bizzoca et al, 2003).…”
Section: Balancing Proliferation and Differentiation In The Externalmentioning
confidence: 99%
“…The IgSF CAMs Contactin1 and Contactin2 were not only shown to guide axons (see above) but also to affect neurogenesis in the cerebellum, the cortex, and also the adult hippocampus (Bizzoca et al 2003 andMa et al, 2008;Xenaki et al, 2011;Puzzo et al, 2013). In order to understand the link between neural development and neurodevelopmental disorders, we will need to take a more integrative look at the role of molecules and mechanisms in neural circuit formation.…”
Section: Syncams As Axon Guidance Molecules In the Pnsmentioning
confidence: 99%
“…Rios et al (2004) propose a model in which BMPs antagonize SHH signaling to promote GCP differentiation over proliferation. More recently, Xenaki et al (2011) have shown that two cell adhesion proteins of the contactin (Cntn) family, Tag-1 (Cntn2) and F3 (Cntn1), are involved in regulating GCP proliferation in the EGL. F3 was shown to promote granule cell differentiation in the EGL by suppressing SHH's positive regulation of GCP proliferation, while TAG-1 helps sustain proliferation (Xenaki et al, 2011).…”
Section: Shox2 Is Important For Maintaining Shh Expression Levels Inmentioning
confidence: 99%
“…More recently, Xenaki et al (2011) have shown that two cell adhesion proteins of the contactin (Cntn) family, Tag-1 (Cntn2) and F3 (Cntn1), are involved in regulating GCP proliferation in the EGL. F3 was shown to promote granule cell differentiation in the EGL by suppressing SHH's positive regulation of GCP proliferation, while TAG-1 helps sustain proliferation (Xenaki et al, 2011). When F3/contactin expression is driven by Tag-1 regulatory sequences, the cerebellum is reduced in size during the first two postnatal weeks of development, presumably because of a reduction in the number of GCPs present in the EGL, and ultimately results in a thinner IGL (Bizzoca et al, 2003).…”
Section: Shox2 Is Important For Maintaining Shh Expression Levels Inmentioning
confidence: 99%
See 1 more Smart Citation